Chapter Dimitri Tsafendas Meets Dante, Friend and Witness of Our Time - Di Florio, Martina (Studi e saggi, 2021)
Chariklia Martalas's "Eating John Vorster" brings to light the assassination of Hendrik Verwoerd, "the architect of Apartheid," by Dimitri Tsafendas. As an act of social responsibility, the author presents the intergenerational trauma of Apartheid to a transnational community of readers. This article, drawing on an interview with Martalas, argues that her reading of Dante's Inferno rewrites a traumatic South African memory as well as transforms the reader into a responsible witness and messenger. Martalas establishes an ideal friendship with Dante and, while powerfully reactivating and rewriting his vivid imagery, unveils a contemporary tragedy. Her creative text addresses the reader's consciousness and questions the interconnection among language, values, and actions.